Pengaruh Kepemimpinan Haedar Nashir dalam Organisasi Muhammadiyah - Fannisa Fatirahma (LP. Ma'arif Janggan Magetan, 2023)
Social religious organization is applied in Indonesia the modern one, is Muhammadiyah where leaders leadership in every period of time have their own special characteristocs which affect the emphasis and vaiation formulation organization the program and activity. Appear a problems draw issue, leadership will affect namely whether in running an organization Kemuhammadiyahan and what was that impact for its members. Writer take one public figure Muhammadiyah, Haedar Nashir. Methods used int his research is a method of inductive. A method of inductive is procedure to draw general conclusions that based on the process of thought after special events or concrete. The data that has been collected critizied, both internal of external, or data so valid and authenticThis study concluded, that Haedar Nashir leadership in Muhammadiyah have influence in the structure of a transformation that indicated at least three influence, the first is idea, second in the struggle and actualization, and the third is facility development.